2011
DOI: 10.3109/03009734.2011.626541
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin II levels in patients with chronic kidney disease and kidney transplants

Abstract: Objective. Urotensin II is a potent vasoactive peptide that has been implicated in the pathophysiology of many diseases. There is no study reporting the role and level of this peptide in recipients of kidney transplant. So we aimed to study the plasma levels of urotensin II in this group of patients.Methods. Plasma urotensin II levels were analyzed in 110 subjects, who were divided into three groups: group 1 (35 kidney transplant recipients), group 2 (36 patients with chronic kidney disease), and group 3 (39 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…This could not be explained solely by the transplanted kidney, because UII levels were higher than healthy controls and It was assumed that this could be immunosuppressive drug-related. However, the immunosuppressive drug doses and the duration of transplantation did not correlate with UII levels [39]. In our study, RTR children had significantly higher UII levels compared to healthy controls and higher but without statistical significance UII levels than CKD patients.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…This could not be explained solely by the transplanted kidney, because UII levels were higher than healthy controls and It was assumed that this could be immunosuppressive drug-related. However, the immunosuppressive drug doses and the duration of transplantation did not correlate with UII levels [39]. In our study, RTR children had significantly higher UII levels compared to healthy controls and higher but without statistical significance UII levels than CKD patients.…”
Section: Discussioncontrasting
confidence: 52%
“…This is in accordance with most of the above mentioned studies [ 9 , 36 , 45 ]. On the contrary, a significant correlation between age and UII has been reported [ 6 ] and Hurshitoglu et al [ 39 ] observed that males tended to have higher levels of UII than females.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggested that it can induce a pro-atherothrombotic phenotype in human coronary endothelial cells and can be used as a biomarker predicting the adverse cardiovascular events. [41,42] Urotensin II (UT-II), which plays an important role in CKD, [43] is involved with endothelial dysfunction and coronary thrombosis. [44] It probably represents a key link between CKD and CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The vasoactive peptide UII has been shown to be increased in several disease conditions as hypertension, heart failure, atherosclerosis, kidney failure, etc. Surprisingly, its plasma levels were found to be higher in patents underwent kidney transplant than chronic renal failure and healthy control subjects [11]. In addition to its vasoactive effect, it also has a diabetogenic effect [3,4].…”
Section: Discussionmentioning
confidence: 97%
“…Routine laboratory tests were performed in our hospital's laboratory and plasma UII level was determined in Ahenk Laboratory (Istanbul, Turkey). The details of blood sample collection for UII and its determination were discussed elsewhere [11].…”
Section: Methodsmentioning
confidence: 99%